2018
DOI: 10.1371/journal.pone.0209744
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges and proposed solutions to the effective implementation of the RTS, S/AS01 Malaria Vaccine Program in sub-Saharan Africa: A systematic review

Abstract: BackgroundThe Malaria Vaccine Implementation Program, coordinated by the World Health Organization, intended to initiate the roll-out of the RTS, S/AS01 malaria vaccine in 3 sub-Saharan African countries in 2018. With sub-optimal implementation, the effectiveness of this vaccine in routine clinical use could be significantly lower than its measured efficacy in randomized trials. This study had as objectives to systematically review and summarize published studies addressing the challenges faced during the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…7 Although great effort has been invested in the identification of protective antigens, previous vaccination strategies have generally been unsatisfactory and only the pre-erythrocytic vaccine RTS,S (Mosquirix TM , GSK Bio), based on the P. falciparum circumsporozoite antigen, is under pilot implementation studies in three African countries. [8][9][10][11] Nonetheless, its efficacy is moderate and short-lived (39% reduction in overall malaria incidence and 31.5% in life-threatening complications over a follow-up period of 48 months in children who received four injections 12,13 ), possibly due to a decay in complement-fixing antibodies. 14 An antigen that has been widely considered as a component of a malaria vaccine is the P. falciparum merozoite surface protein 1 (MSP1).…”
Section: Introductionmentioning
confidence: 99%
“…7 Although great effort has been invested in the identification of protective antigens, previous vaccination strategies have generally been unsatisfactory and only the pre-erythrocytic vaccine RTS,S (Mosquirix TM , GSK Bio), based on the P. falciparum circumsporozoite antigen, is under pilot implementation studies in three African countries. [8][9][10][11] Nonetheless, its efficacy is moderate and short-lived (39% reduction in overall malaria incidence and 31.5% in life-threatening complications over a follow-up period of 48 months in children who received four injections 12,13 ), possibly due to a decay in complement-fixing antibodies. 14 An antigen that has been widely considered as a component of a malaria vaccine is the P. falciparum merozoite surface protein 1 (MSP1).…”
Section: Introductionmentioning
confidence: 99%
“…RTS,S/AS01 vaccine is a pre-erythrocytic stage vaccine based on the P. falciparum circumsporozoite protein (PfCSP) [4,5]. In 2015, the European Medicines Agency for the immunization of children against malaria approved the RTS, S/AS01 vaccine [6] and the phase 3 clinical trials conducted in various sites in Africa showed that the RTS, S/AS01 vaccine has a protective e cacy of 45% in children in the rst twenty months after vaccination [7,8]. In 2018, the World Health Organization through a large-scale pilot malaria vaccine implementation program (MVIP) aimed to introduce this vaccine in three sub-Saharan countries (Ghana, Kenya, Malawi) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the European Medicines Agency for the immunization of children against malaria approved the RTS, S/AS01 vaccine [6] and the phase 3 clinical trials conducted in various sites in Africa showed that the RTS, S/AS01 vaccine has a protective e cacy of 45% in children in the rst twenty months after vaccination [7,8]. In 2018, the World Health Organization through a large-scale pilot malaria vaccine implementation program (MVIP) aimed to introduce this vaccine in three sub-Saharan countries (Ghana, Kenya, Malawi) [6]. Besides of RTS,S/AS01, a live attenuated Plasmodium falciparum whole sporozoite (SPZ) vaccine is also regarded as a great potential malarial vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…This may be especially useful in overcoming communities' myths and fears about new vaccines, which are often considerably more expensive than existing ones, and target relatively 'hidden' diseases [31,32]. However, current CE evidence is limited to a few systematic examinations focused on community counselling and vaccination campaigns, often in pockets of high vaccine resistance and low vaccination coverage [33,34]. These reviews have also focused on public opposition rather than involvement, and no data have been collected to indicate if and how communities are engaged beyond individuals' decisions to vaccinate themselves and their children [35,36,37].…”
Section: Introductionmentioning
confidence: 99%